Analisis Strategi Pemasaran Media Sosial pada Waralaba D’Potachiz Gor H Agus Salim Kota Padang - Dewi Susanti; Himmatul Khairi (Lembaga Yasin AlSys, 2026)
Although social media marketing strategies have received attention in various studies, research that specifically discusses their implementation in small-scale franchise businesses remains limited. This study aims to analyze the social media marketing strategies implemented, identify constraints in their implementation, and formulate alternative solutions to improve marketing effectiveness at the D’potachiz franchise at GOR H. Agus Salim, Padang City. This study employed a qualitative approach with a case study design. The informants consisted of the business owner, employees, and consumers who were selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results showed that the implemented social media marketing strategy had not been systematically structured, as indicated by the absence of scheduled content planning, limited content variation, and suboptimal interaction with consumers. The main constraints included limited ability to create creative content, time constraints, and a lack of consistency in social media management. The solutions that can be undertaken include improving content quality, planning posts more systematically, and increasing interaction with consumers. These findings contribute to the development of digital marketing studies, particularly in small businesses, and provide practical implications for business actors in optimizing social media marketing strategies. This study also opens opportunities for broader and more measurable further research.